The Fourth Dimension The Space, Rhythm, and Time in the interior Design - Tayib, Abdullah; Issa, Naram Murqis (Sulaimani Journal for Engineering Sciences, 2015)
The Interior spaces are the essential requirements of comfort for human; they interact strongly with all the requirements which provide the basic factors that the human pursue in choosing a certain space within a set of spaces. The human interacts with the space in which he spend most times of his days, so it is supposed that the movement be the assistant factor which provides the wright and successful pathways that work on the connecting between the interaction points in order to generate the secondary times which being added to the total time. Because of the importance of this subject the research chose the relationship between rhythm and time as a final product for all the events that take place in the interior space, the research problem appears which is represented by (the lack of knowledge with respect to the design characteristics and the perceptions of the recipient in the Interior spaces;) It is possible to formulate the assumption study sample default with respect to the interior spaces by the following main hypothesis “The design characteristics represented by the elements and principles forming the interior spaces which effect on the recipient’s perception to form a set of the visual scenes and events that arrange in accordance with the principle of rhythm affecting on the time factor in those spaces.” And the aim of research represents by” finding the relationship between the interior spaces and the fourth dimension represented by the time”.
Keywords: Fourth dimension; time; space; interior design